WORK-FAMILY CONFLICT AND BURNOUT IN FRONTLINE SERVICE JOBS: DIRECT, MEDIATING AND MODERATING EFFECTS - Karatepe, Osman M.; Sokmen, Alptekin; Yavas, Ugur; Babakus, Emin (Technical Univ Liberec, 2010)
This study develops and tests a model where work-family conflict is posited as a mediator between work overload and burnout (exhaustion and disengagement), and positive affectivity as a moderator of the relationships between work overload, and work-family conflict and burnout. Data for the study were collected from a sample of 620 full-time frontline hotel employees in Turkey. Hierarchical multiple regression analysis was employed in analyzing the data. The results show that work-family conflict fully mediates the impacts of work overload on exhaustion and disengagement. Also positive affectivity reduces the effect of work-family conflict on disengagement. Implications of the empirical results and directions for future research are delineated in the study. In this study we develop a model and test eight hypotheses that are based on the precepts of the Conservation of Resources (COR) theory [16]. We contend that work overload is a predictor of work-family conflict which influences the two dimensions of burnout (exhaustion and disengagement). In other words, our model proposes that work-family conflict acts as a full mediator between work overload and the burnout dimensions. In the remainder of the paper, we present our hypotheses. This is followed by discussions of the method and findings of our empirical study. We conclude with implications of the results and directions for future research.
Keywords: burnout; frontline employees; Turkey; work-family conflict; work overload